A Phosphorylatable Sphingosine Analog Induces Airway Smooth Muscle Cytostasis and Reverses Airway Hyperresponsiveness in Experimental Asthma - Gendron, David R.; Lecours, Pascale B.; Lemay, Anne-Marie; Beaulieu, Marie-Josée; Huppé, Carole-Ann; Lee-Gosselin, Audrey; Flamand, Nicolas; Don, Anthony S.; Bissonnette, Élyse; Blanchet, Marie-Renée; Laplante, Mathieu; Bourgoin, Sylvain G.; et al. (Frontiers in Pharmacology, 2017)
In asthma, excessive bronchial narrowing associated with thickening of the airway smooth muscle causes respiratory distress. Numerous pharmacological agents prevent experimental airway hyperresponsiveness when delivered prophylactically. However, most fail to resolve this feature after disease is instated. Although sphingosine analogs are primarily perceived as immune modulators with the ability to prevent experimental asthma, they also influence processes associated with tissue atrophy, supporting the hypothesis that they could interfere with mechanisms sustaining pre-established airway hyperresponsiveness. We thus assessed the ability of a sphingosine analog (AAL-R) to reverse airway hyperresponsiveness in a chronic model of asthma. We dissected the pharmacological mechanism of this class of agents using the non-phosphorylatable chiral isomer AAL-S and the pre-phosphorylated form of AAL-R (AFD-R) in vivo and in human airway smooth muscle cells. We found that a therapeutic course of AAL-R reversed experimental airway hyperresponsiveness in the methacholine challenge test, which was not replicated by dexamethasone or the non-phosphorylatable isomer AAL-S. AAL-R efficiently interfered with airway smooth muscle cell proliferation in vitro, supporting the concept that immunomodulation is not necessary to interfere with cellular mechanisms sustaining airway hyperresponsiveness. Moreover, the sphingosine-1-phosphate lyase inhibitor SM4 and the sphingosine-1-phosphate receptor antagonist VPC23019 failed to inhibit proliferation, indicating that intracellular accumulation of sphingosine-1-phosphate or interference with cell surface S1P1/S1P3 activation, are not sufficient to induce cytostasis. Potent AAL-R-induced cytostasis specifically related to its ability to induce intracellular AFD-R accumulation. Thus, a sphingosine analog that possesses the ability to be phosphorylated in situ interferes with cellular mechanisms that beget airway hyperresponsiveness.